The labor market in Germany, 2000-2018 - Hilmar Schneider; Ulf Rinne (IZA World of Labor, 2019)
The EU's largest economy, Germany, has managed to find an effective and unique combination of flexibility and rigidity in its labor market. Institutions that typically characterize rigid labor markets are effectively balanced by flexibility instruments. Important developments since 2000 include steadily decreasing unemployment rates (since 2005), increasing participation rates, and (since 2011) moderately increasing labor compensation. The German labor market was remarkably robust to the impacts of the Great Recession, thus providing a useful case study for other developed countries.
Keywords: E23; M53; 330; wages; unemployment; Germany; vocational training; regulation